The factors influencing the supply of rural elderly services in China based on CHARLS data: Evidence from rural land use and management - Zhao, Yan (Frontiers in Environmental Science, 2022)
The problem of elderly service supply is a important issue that must be solved for the development of an aging society. This study uses microdata from the China Health and Retirement Longitudinal Study that were published in 2017 and from a regression analysis using a dichotomous logistic model. Finally, the article examines the factors that affect the supply of elderly services and land use in rural China. The results show that 1) the health level is the most direct influencing factor on whether rural elderly people in rural land can obtain elderly services; 2) the family characteristics that affects the supply of elderly services in rural land is the relationship of living with children rather than the number of children; 3) socio-economic status has an impact on the supply of elderly services, but this impact is limited; and 4) the factors affecting the supply of family elderly services and social elderly services for the rural elderly are basically the same, with the fundamental difference between the two being that the service targets are different, which reflects typological characteristics.